Tracing flow directions of the Pentung Allogenic River in Gunungsewu Karst Area, Gunungkidul, using artificial tracer test - Cahyadi, A. (Institute of Physics, 2022)
Previous studies in the Gunungsewu Karst Area categorized the Pentung Allogenic River catchment that drains to the Sawah Ombo Pond as the upper part of the Bribin Karst Drainage Basin (KDB). However, more detailed results from natural isotope studies after 2010 have provided reasons to postulate that the groundwater does not flow from the catchment to Bribin KDB. Therefore, the research aimed to trace the direction of Pentung's groundwater flows in Gunungsewu's karstic hydrogeological system. To achieve this, an artificial tracer test was used. There were two fluorescent dye injection namely uranine and tinopal. The results confirmed that the allogenic river's catchment supplied groundwater to Beton KDB instead of Bribin KDB. While the artificial tracers were not detected in the water at Gilap Cave and Bribin Underground River, they appeared in Jomblangan Cave and Sriti Spring, parts of Beton KDB. © Published under licence by IOP Publishing Ltd.